Building a No Cost Undergraduate Community Speech Clinic - Meagan Spencer; Mary Beth Seibel; Emily Beard; Emily Christensen (Journal of Student-Run Clinics, 2024)
Aim: This study aimed to explore the clinic learning models through student perspectives using that insight to explore how these students viewed a newly established speech clinic program and understand the organizational and learning benefits and limitations of the clinic and how it can be improved for future service for student learning.Methods: This exploratory study utilized an observation analysis to understand how the student-led functioning of the clinic fits into both the learning models of Bloom’s Taxonomy and Bandura’s Triadic Reciprocal Model of Causality and the factors that contribute most to these learning models. These models were chosen due to the systemic and progressive nature of learning that reflects the academic mission of the university’s accrediting body: the Southern Association of Colleges and Schools Commission on Colleges. A mixed closed and open-ended student questionnaire was utilized to gain insight into themes that influence the student-led learning model.Results: The clinic was overall seen as a place of relationship building and skills development. The main contributors to this relationship-building and skills development lie in the ability of students to apply what they have been learning in the classroom to a functional situation, as well as the opportunity to serve the community and build confidence and leadership skills.Conclusion: Student leadership roles in the clinic are leading to self-efficacy which is seen in the highest level of Bloom’s Taxonomy and Bandura’s Triadic Reciprocal Model of Causality.